[Retracted] Combined Case of Blood-Injury-Injection Phobia and Social Phobia: Behavior Therapy Management and Effectiveness through Tilt Test - Ferenidou, Fotini; Chalimourdas, Theodoros; Antonakis, Velissarios; Vaidakis, Nikolaos; Papadimitriou, Georgios (Case Reports in Psychiatry, 2012)
The efficacy of behavior therapy based mainly on real-life exposure situations as well as applied tension was examined for a combined case of blood-injury-injection (BII) phobia and social anxiety disorder. Treatment involved 28 behavior therapy sessions, while applied tension technique was also described and practiced. The specific contribution of social skills techniques, fantasy, and real-life situations exposure was examined in a single case design. The subject was a 39-year-old male with anxiety symptoms when confronting an audience, as well as symptoms of the autonomic nervous system (bradycardia and syncope), which were better explained by BII. All self-report measures regarding fear, social phobia, and anxiety were reduced after behavior therapy and remained maintained at followup, while BII decreased further after applied tension techniques. The contribution of behavior therapy to the overall outcome of the case is considered significant for many reasons that are discussed in the pape.